Tanggung Jawab Pemerintah Daerah terhadap Pemenuhan Sarana dan Prasarana Pendidikan Dasar Perspektif Hukum Positif dan Fiqh Siyasah - Sonya Noprisa Sumantri; Dhiauddin Tanjung (Kartika: Jurnal Studi Keislaman, 2026)
The provision of basic education facilities and infrastructure constitutes part of local government responsibility to guarantee the right to education as mandated by the 1945 Constitution, Law No. 20/2003, and Law No. 23/2014. However, implementation at SD Negeri 040485 and SD Negeri 040486 Gurukinayan, Karo Regency, faces challenges due to inadequate facilities affecting the learning process. This study aims to analyze the implementation of Karo Regency Government's responsibility, identify obstacles, and examine the issue from Fiqh Siyasah perspective. This research employed empirical juridical method with statutory, empirical, and Fiqh Siyasah approaches. Findings indicate that implementation has not been optimal, reflected in damaged classrooms, insufficient desks and chairs, inadequate toilets, and limited teaching aids. Main obstacles include budget constraints, geographical conditions, suboptimal needs assessment, and weak monitoring and distribution of educational assistance. From Fiqh Siyasah perspective, these conditions demonstrate that principles of amanah (trustworthiness), justice, leadership accountability, and maslahah (public welfare) have not been fully realized in delivering basic education services